Microbial ‘old friends’, immunoregulation and socioeconomic status - Rook, G A W (Blackwell Science Inc, 2014)
The immune system evolved to require input from at least three sources that we collectively term the ‘old friends’: (i) the commensal microbiotas transmitted by mothers and other family members; (ii) organisms from the natural environment that modulate and diversify the commensal microbiotas; and (iii) the ‘old’ infections that could persist in small isolated hunter-gatherer groups as relatively harmless subclinical infections or carrier states. These categories of organism had to be tolerated and co-evolved roles in the development and regulation of the immune system. By contrast, the ‘crowd infections’ (such as childhood virus infections) evolved later, when urbanization led to large communities. They did not evolve immunoregulatory roles because they either killed the host or induced solid immunity, and could not persist in hunter-gatherer groups. Because the western lifestyle and medical practice deplete the ‘old’ infections (for example helminths), immunoregulatory disorders have increased, and the immune system has become more dependent upon microbiotas and the natural environment. However, urbanization maintains exposure to the crowd infections that lack immunoregulatory roles, while accelerating loss of exposure to the natural environment. This effect is most pronounced in individuals of low socioeconomic status (SES) who lack rural second homes and rural holidays. Interestingly, large epidemiological studies indicate that the health benefits of living close to green spaces are most pronounced for individuals of low SES. Here we discuss the immunoregulatory role of the natural environment, and how this may interact with, and modulate, the proinflammatory effects of psychosocial stressors in low SES individuals.